A Study on the Impact of Inflation, Poverty, and Unemployment on Income Inequality at Cermin Beach, Serdang Bedagai Regency - Ridwan, Aldy; Lubis, Fauzi Arif; Tambunan, Khairina (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
One of the causes of income inequality is the large number of poor and unemployed people. The relationship between inflation, poverty, unemployment and income inequality shows a continuous interaction of these three factors. The aim is to determine the effect of inflation, poverty and unemployment on income inequality in the district. Mirror Beach, Kab. Serdang Bedagai. The data used is secondary data obtained from the Central Statistics Agency (BPS) for the 2019-2023 time period. The analytical method used is quantitative). The software used for analysis is spss 26.0. The research results show that the inflation variable has an effect on income inequality. The poverty variable has no effect on income inequality, the unemployment variable has an effect on income inequality and together the inflation, poverty and unemployment variables have a significant effect on income inequality in the district. Cermin Beach, Kab. Serdang Bedagai.